Wave-absorbing aerogel capable of being cyclically compressed and rebounded and preparation method thereof
By electrostatically assembling nanosheets and nanofibers and adding binder, an aerosol absorbing aerogel with cyclic compression rebound characteristics was constructed, which solved the problem of the decay of the absorption performance of existing aerogels under high compression strain conditions, and achieved efficient electromagnetic wave absorption and good mechanical rebound.
Patent Information
- Application Number
- CN202411923755.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
The existing aerogel materials are difficult to maintain wave absorption performance under high compression strain conditions and have limited recovery capabilities, which limits their application in situations where they are subjected to large pressures or frequent compression deformation.
The nanosheet/nanofiber basic structural unit is formed by electrostatic assembly, and a binder is added between the sheet/fiber structural unit to form a stable bonding point, thereby constructing a wave absorbing aerogel with cyclic compression rebound characteristics.
It realizes that the aerogel can rebound to its original size after 30% compression strain, and maintains good mechanical rebound after 50 compression cycles, while improving its absorbance performance, reaching a minimum reflection loss of -44.9 dB and an effective absorption bandwidth of 9.5 GHz.
Smart Images

Figure CN119751963A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wave-absorbing materials, and relates to a wave-absorbing aerogel capable of cyclic compression and rebound. The invention also relates to a method for preparing the wave-absorbing aerogel. Background Art
[0002] As a material with low density, high porosity and large specific surface area, aerogel has shown great application potential in the field of electromagnetic wave absorption due to its unique physical and chemical properties. Its rich internal microporous structure can effectively cause multiple reflections, scattering and interference of electromagnetic waves inside the material, thereby effectively absorbing electromagnetic waves. In addition, the skeleton structure of aerogel can be functionally designed by regulating its preparation process to further improve its wave absorption performance. This makes aerogel likely to become an indispensable electromagnetic protection material in future communication equipment.
[0003] Despite its excellent performance in wave absorption, aerogels still have some deficiencies in compressibility and resilience in practical applications. Especially under high compression strain conditions, existing aerogel materials often find it difficult to maintain their original wave absorption performance, and their recovery ability is limited after being subjected to external forces. This limits the application of aerogels in some situations that require high pressure or frequent compression deformation. To this end, researchers have tried to use flexible nanostructures such as nanosheets, nanotubes, and nanofibers as basic units to develop a series of aerogels with certain compression and rebound properties. However, these materials generally have the problems of low compression strength and insufficient load-bearing capacity. While improving the load-bearing capacity of aerogels, it is often accompanied by a decrease in deformation capacity, resulting in many challenges in practical applications. Summary of the invention
[0004] The purpose of the present invention is to provide a wave-absorbing aerogel capable of cyclic compression and rebound, thereby solving the problem of insufficient compression rebound elasticity due to the destruction of the porous structure of the aerogel in the prior art and avoiding the degradation of the wave-absorbing performance of the aerogel.
[0005] Another object of the present invention is to provide a method for preparing a wave-absorbing aerogel capable of cyclic compression and rebound.
[0006] The technical solution adopted by the present invention is an absorbing aerogel that can be cyclically compressed and rebounded. The three-dimensional porous framework of the absorbing aerogel is constructed by nanofibers, nanosheets and a binder. The nanosheets and nanofibers are electrostatically assembled to form sheet / fiber basic structural units, and the binder forms stable bonding points between the sheet / fiber structural units.
[0007] The second technical solution adopted by the present invention is a method for preparing a wave-absorbing aerogel capable of cyclic compression and rebound. The preparation of the wave-absorbing aerogel capable of cyclic compression and rebound is specifically carried out according to the following steps: Step 1, mixing a polymer precursor, a spinning aid and a solvent to prepare a spinning solution and performing electrospinning, and then sequentially performing a thermal oxidation crosslinking reaction and a polymer conversion reaction on the electrospun product to obtain nanofibers; Step 2, chemically modifying the nanofibers obtained in step 1 so that their surfaces are positively charged, and then remixing with the negatively charged nanosheet solution to obtain a sheet / fiber composite solution through electrostatic assembly, wherein the components of the sheet / fiber composite solution are the sheet / fiber basic structural units; Step 3, adding a binder to the sheet / fiber composite solution obtained in step 2, stirring evenly to obtain a mixture, directionally freezing the mixture, and obtaining a sheet / fiber composite aerogel by supercritical drying.
[0008] The second technical solution of the present invention is also characterized in that: In step 1, the polymer precursor is polyborosilazane; the spinning aid is polyvinyl pyrrolidone, and the solvent is a mixture of chloroform and N,N-dimethylformamide; The weight percentage of the polymer precursor in the spinning solution is 30 wt.%, the weight percentage of polyvinyl pyrrolidone is 10 wt.%, the weight percentage of chloroform is 45 wt.%, and the weight percentage of N,N-dimethylformamide is 15 wt.%.
[0009] The process parameters of electrospinning in step 1 are: spinning voltage 15-25 kV, receiving distance 15-20 cm, spinning rate 0.5-1.5 ml / h, spinning needle diameter 0.5-1.0 mm, spinning temperature 20-30°C, and spinning environment humidity 40-60%.
[0010] The temperature of the thermal oxidation crosslinking reaction in step 1 is 200-300° C. and the time is 0.5-1 h; The temperature of the polymer conversion reaction in step 1 is 1200-1500° C. and the time is 2-4 hours.
[0011] The chemical modifier used in the chemical modification in step 2 is any one of dopamine hydrochloride, hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, ethylenediamine, and hexamethylenetetramine, and the solvent is a mixture of deionized water and anhydrous ethanol; The concentration of chemical modifier was 10 mg / mL, the mass ratio of deionized water and anhydrous ethanol was 1:1, and the mass ratio of chemical modifier and nanofibers was 1:1; The modification time used in the chemical modification is 6-12 hours, the modification temperature is 20-50° C., and the stirring speed is 300-600 rpm.
[0012] The nanosheets used for electrostatic assembly in step 2 are any one of graphene, MXene, and MoS2, the concentration of the nanosheet solution is 10 mg / mL, the solvent is deionized water, and the added mass ratio of nanofibers and nanosheets is 1:1-4:1.
[0013] In step 3, the binder is polyvinyl alcohol, the mass ratio of polyvinyl alcohol to nanosheets is 3:1, the stirring temperature is 70° C., and the stirring time is 12 h.
[0014] The directional freezing in step 3 adopts a bidirectional freezing process, and the mold used for freezing is made of copper and has a wedge shape.
[0015] The beneficial effects of the present invention are: (1) The absorbing aerogel provided by the present invention has extremely low density and good impedance matching. The porous structure plays a role in scattering and reflection, greatly extending the transmission path of electromagnetic waves. A heterogeneous interface is formed between the nanosheets and nanofibers, which promotes polarization loss. According to electromagnetic calculations, the minimum reflection loss of the aerogel prepared by the present invention reaches -44.9 dB (at 8.96 GHz), and the effective absorption bandwidth is 9.5 GHz (thickness is 1.25 mm), covering more than 95% of the X-band and Ku-band.
[0016] (2) The present invention assembles nanosheets and nanofibers through electrostatic assembly to form a sheet / fiber basic structural unit, which has a similar effect to that of a steel bar / concrete structure, and can simultaneously improve the strength and toughness of the porous structure to improve the strength of the aerogel; a binder is used to form a stable bonding point between the sheet / fiber structural units, thereby giving the aerogel good cyclic compression and rebound properties. The aerogel prepared by the present invention can still rebound to its original size after a 30% compression strain, and still has good mechanical resilience after 50 compression cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 is a scanning electron microscope image of the basic structural unit of the sheet / fiber prepared in Example 5 of the present invention; Figure 2 Schematic diagram of the structure of the cyclically compressible and resilient wave-absorbing aerogel prepared in Example 5 of the present invention; Figure 3 is a minimum reflection loss diagram of the cyclically compressible and resilient wave-absorbing aerogel prepared in Example 5 of the present invention; Figure 4 It is a stress / strain curve diagram of the cyclically compressed and resilient wave-absorbing aerogel prepared in Examples 3-6 of the present invention. DETAILED DESCRIPTION
[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0019] Example 1 The invention discloses an absorbing aerogel capable of cyclic compression and rebound. The three-dimensional porous framework of the absorbing aerogel is constructed by nanofibers, nanosheets and a binder. The nanosheets and nanofibers are assembled by electrostatics to form sheet / fiber basic structural units, and the binder forms stable bonding points between the sheet / fiber structural units.
[0020] Example 2 The method for preparing the cyclically compressed and resilient absorbing aerogel of the present invention is to prepare the cyclically compressed and resilient absorbing aerogel in Example 1, and the method is specifically implemented according to the following steps: Step 1, mixing a polymer precursor, a spinning aid and a solvent to prepare a spinning solution and performing electrostatic spinning, and then sequentially performing a thermal oxidation crosslinking reaction and a polymer conversion reaction on the electrostatic spinning product to obtain nanofibers; wherein the polymer precursor is polyborosilazane; the spinning aid is polyvinyl pyrrolidone, and the solvent is a mixture of chloroform and N,N-dimethylformamide; The weight percentage of the polymer precursor in the spinning solution is 30 wt.%, the weight percentage of polyvinyl pyrrolidone is 10 wt.%, the weight percentage of chloroform is 45 wt.%, and the weight percentage of N,N-dimethylformamide is 15 wt.%; The process parameters of electrospinning are: spinning voltage 15-25 kV, receiving distance 15-20 cm, spinning rate 0.5-1.5 ml / h, spinning needle diameter 0.5-1.0 mm, spinning temperature 20-30℃, spinning environment humidity 40-60%; The temperature of the thermal oxidation crosslinking reaction is 200-300°C and the time is 0.5-1h; The temperature of the polymer conversion reaction is 1200-1500°C and the time is 2-4h; Step 2, chemically modify the nanofibers obtained in step 1 so that their surface is positively charged, and then mix with the negatively charged nanosheet solution to obtain a sheet / fiber composite solution, the components of which are the basic structural units of the sheet / fiber. Among them, the chemical modifier is any one of dopamine hydrochloride, hexadecyltrimethylammonium bromide, dodecyldimethylbenzyl ammonium chloride, ethylenediamine, and hexamethylenetetramine, and the solvent is a mixture of deionized water and anhydrous ethanol. The concentration of the chemical modifier is 10 mg / mL, the mass ratio of deionized water and anhydrous ethanol is 1:1, the mass ratio of the chemical modifier and the nanofiber is 1:1, the modification time used in the chemical modification is 6-12h, the modification temperature is 20-50°C, and the stirring rate is 300-600rpm.
[0021] The nanosheets used in the electrostatic assembly are any one of graphene, MXene, and MoS2, the concentration of the nanosheet solution is 10 mg / mL, the solvent is deionized water, and the added mass ratio of nanofibers and nanosheets is 1:1-4:1.
[0022] Step 3, adding polyvinyl alcohol as a binder to the nanosheet / nanofiber composite solution obtained in step 2, the mass ratio of polyvinyl alcohol to nanosheet is 3:1, and the mixture is obtained by uniform stirring, the stirring temperature is 70°C, and the stirring time is 12h. The mixture is directionally frozen, the freezing method is bidirectional freezing, and the mold used during freezing is made of copper and has a wedge shape. The nanosheet / nanofiber composite aerogel is obtained by supercritical drying.
[0023] Example 3 On the basis of Example 2, S1, 30 g of polyborosilazane (PBSZ), 10 g of polyvinyl pyrrolidone (PVP), 45 g of chloroform (CHCl3), and 15 g of N,N-dimethylformamide (DMF) were measured in a beaker and mixed to prepare a spinning solution. Electrospinning was performed under the conditions of voltage 25 kV, receiving distance 20 cm, spinning rate 1.5 ml / h, needle diameter 1.0 mm, spinning temperature 30°C, and ambient humidity 60%. The thermal oxidation crosslinking temperature was set to 300°C for 1 h. The polymer conversion temperature was 1500°C for 4 h. S2, 0.5 g of dopamine hydrochloride was dissolved in a mixture of 25 ml of deionized water and 25 ml of anhydrous ethanol, and then 0.5 g of nanofibers were added for chemical modification. The modification time was 12 h, the modification temperature was 50 ° C, and the stirring rate was 600 rpm. After centrifugation, washing and drying, chemically modified nanofibers were obtained. 0.5 g of graphene was dispersed in 50 ml of deionized water to obtain a graphene solution, and then 2.0 g of chemically modified nanofibers were added. The solution was stirred continuously at 50 ° C for 6 h to obtain a nanosheet / nanofiber composite solution. The components of the sheet / fiber composite solution are the sheet / fiber basic structural units.
[0024] S3, add 1.5 g of polyvinyl alcohol (PVA) as a binder to the sheet / fiber composite solution obtained in S2, and stir continuously at 70°C for 12 hours to obtain a mixture. The mixture is subjected to directional freezing, and the freezing method is bidirectional freezing. The mold used during freezing is made of copper and has a wedge shape. The sheet / fiber composite aerogel is obtained by supercritical drying.
[0025] Example 4 On the basis of Example 2, S1, 30 g of polyborosilazane (PBSZ), 10 g of polyvinyl pyrrolidone (PVP), 45 g of chloroform (CHCl3), and 15 g of N,N-dimethylformamide (DMF) were measured in a beaker and mixed to prepare a spinning solution. Electrospinning was performed under the conditions of voltage 15 kV, receiving distance 15 cm, spinning rate 0.5 ml / h, needle diameter 0.5 mm, spinning temperature 20°C, and ambient humidity 40%. The thermal oxidation crosslinking temperature was set to 200°C and the time was 0.5h. The polymer conversion temperature was 1200°C and the time was 2h.
[0026] S2, 0.5 g of hexadecyltrimethylammonium bromide was dissolved in a mixture of 25 ml of deionized water and 25 ml of anhydrous ethanol, and then 0.5 g of nanofibers were added for chemical modification. The modification time was 6 h, the modification temperature was 20 ° C, and the stirring rate was 300 rpm. After centrifugation, washing and drying, chemically modified nanofibers were obtained. 0.5 g of MXene was dispersed in 50 ml of deionized water to obtain a MXene solution, and then 0.5 g of chemically modified nanofibers were added. The solution was stirred continuously at 50 ° C for 6 h to obtain a sheet / fiber composite solution. The components of the sheet / fiber composite solution are the basic structural units of the sheet / fiber.
[0027] S3, add 1.5 g of polyvinyl alcohol (PVA) as a binder to the sheet / fiber composite solution obtained in S2, and stir continuously at 70°C for 12 hours to obtain a mixture. The mixture is subjected to directional freezing, and the freezing method is bidirectional freezing. The mold used during freezing is made of copper and has a wedge shape. The sheet / fiber composite aerogel is obtained by supercritical drying.
[0028] Example 5 On the basis of Example 2, S1, 30 g of polyborosilazane (PBSZ), 10 g of polyvinyl pyrrolidone (PVP), 45 g of chloroform (CHCl3), and 15 g of N,N-dimethylformamide (DMF) were measured in a beaker and mixed to prepare a spinning solution. Electrospinning was performed under the conditions of voltage 18 kV, receiving distance 16 cm, spinning rate 0.8 ml / h, needle diameter 0.5 mm, spinning temperature 24°C, and ambient humidity 48%. The thermal oxidation crosslinking temperature was set to 240°C and the time was 0.7h. The polymer conversion temperature was 1300°C and the time was 2.5h.
[0029] S2, 0.5 g of dodecyl dimethyl benzyl ammonium chloride was dissolved in a mixture of 25 ml of deionized water and 25 ml of anhydrous ethanol, and then 0.5 g of nanofibers were added for chemical modification. The modification time was 8 h, the modification temperature was 30 ° C, and the stirring rate was 400 rpm. After centrifugation, washing and drying, chemically modified nanofibers were obtained. 0.5 MoS2 was dispersed in 50 ml of deionized water to obtain MoS2 solution, and then 1.0 g of chemically modified nanofibers was added. The solution was stirred continuously at 50 ° C for 6 h to obtain a sheet / fiber composite solution. The components of the sheet / fiber composite solution are the basic structural units of the sheet / fiber.
[0030] S3, add 1.5 g of polyvinyl alcohol (PVA) as a binder to the sheet / fiber composite solution obtained in S2, and stir continuously at 70°C for 12 hours to obtain a mixture. The mixture is subjected to directional freezing, and the freezing method is bidirectional freezing. The mold used during freezing is made of copper and has a wedge shape. The sheet / fiber composite aerogel is obtained by supercritical drying.
[0031] Example 6 On the basis of Example 2, S1, 30 g of polyborosilazane (PBSZ), 10 g of polyvinyl pyrrolidone (PVP), 45 g of chloroform (CHCl3), and 15 g of N,N-dimethylformamide (DMF) were measured in a beaker and mixed to prepare a spinning solution. Electrospinning was performed under the conditions of voltage 12 kV, receiving distance 18 cm, spinning rate 1.2 ml / h, needle diameter 0.8 mm, spinning temperature 28°C, and ambient humidity 55%. The thermal oxidation crosslinking temperature was set to 280°C for 0.8 h. The polymer conversion temperature was 1400°C for 3 h.
[0032] S2, 0.5 g of ethylenediamine was dissolved in a mixture of 25 ml of deionized water and 25 ml of anhydrous ethanol, and then 0.5 g of nanofibers were added for chemical modification. The modification time was 10 h, the modification temperature was 40 ° C, and the stirring rate was 500 rpm. After centrifugation, washing and drying, chemically modified nanofibers were obtained. 0.5 g of MXene was dispersed in 50 ml of deionized water to obtain a MXene solution, and then 1.5 g of chemically modified nanofibers were added. The solution was stirred continuously at 50 ° C for 6 h to obtain a sheet / fiber composite solution. The components of the sheet / fiber composite solution are the basic structural units of the sheet / fiber.
[0033] S3, add 1.5 g of polyvinyl alcohol (PVA) as a binder to the sheet / fiber composite solution obtained in S2, and stir continuously at 70°C for 12 hours to obtain a mixture. The mixture is subjected to directional freezing, and the freezing method is bidirectional freezing. The mold used during freezing is made of copper and has a wedge shape. The sheet / fiber composite aerogel is obtained by supercritical drying.
[0034] As shown in Table 1, the performance test results of Examples 3-6 of the present invention are shown, wherein the compression strength recovery rate test is the compression strength recovery rate obtained by testing the aerogel sample prepared in the corresponding example under a load of 200 N stress and 30% strain after 50 compression cycles; it can be seen from Table 1 that with the increase of nanofiber content, the density of the aerogel gradually increases, the minimum reflection loss is significantly improved, and when the sheet / fiber mass ratio is 1:3, the optimal wave absorbing performance is shown. At the same time, with the increase of nanofiber content, the compression strength is gradually improved, and when the sheet / fiber mass ratio is 1:3, the optimal mechanical rebound performance is shown.
[0035] Table 1
[0036] like Figure 1 As shown in FIG. 5 , it is a scanning electron microscope image of the basic structural unit of the sheet / fiber of the cyclically compressible and resilient wave-absorbing aerogel prepared in Example 5. Figure 1 It can be seen that through electrostatic assembly, the sheets / fibers form basic structural units, showing a composite similar to the steel / concrete structure, which can simultaneously improve the strength and toughness of the porous structure. In addition, a heterogeneous interface is formed between the sheets / fibers, which promotes the interface polarization loss capacity of the aerogel and effectively improves the wave absorption performance of the aerogel.
[0037] like Figure 2 , which shows a schematic diagram of the structure of the cyclic compression and rebound-absorbing aerogel prepared in Example 5. As can be seen from the figure, the aerogel presents a regular continuous pore structure, which allows most of the incident electromagnetic waves to smoothly enter the material and undergo multiple reflections and scattering in its porous structure, ultimately effectively dissipating the electromagnetic wave energy. In addition, the binder forms a stable bonding point between the sheet / fiber structural units, thereby giving the aerogel excellent cyclic compression and rebound properties.
[0038] like Figure 3 As shown in the figure, it is the minimum reflection loss diagram of the cyclically compressible and resilient wave-absorbing aerogel prepared in Example 5. Figure 3 It can be seen that the minimum reflection loss of the aerogel prepared in this embodiment reaches -44.9 dB (at 8.96 GHz), and the effective absorption bandwidth is 9.5 GHz (thickness is 1.25 mm), covering more than 95% of the X-band and Ku-band.
[0039] like Figure 4 As shown, the stress / strain curve of the cyclic compression and rebound absorbing aerogel prepared in Example 3-6 is shown. Figure 4 It can be seen that the aerogel sample prepared in this embodiment shows excellent compression rebound effect under a load of 200 N stress and 30% strain. After 50 compression cycles, the compression strength recovery rate can reach up to 96%.
Claims
1. A wave-absorbing aerogel capable of cyclic compression and rebound, characterized in that: The three-dimensional porous framework of the wave-absorbing aerogel is constructed by nanofibers, nanosheets and a binder. The nanosheets and nanofibers are assembled by electrostatics to form sheet / fiber basic structural units, and the binder forms stable bonding points between the sheet / fiber structural units.
2. A method for preparing a wave-absorbing aerogel capable of cyclic compression and rebound, characterized in that: The preparation of the cyclically compressible and resilient wave-absorbing aerogel as claimed in claim 1 is specifically carried out according to the following steps: Step 1, mixing a polymer precursor, a spinning aid and a solvent to prepare a spinning solution and performing electrospinning, and then sequentially performing a thermal oxidation crosslinking reaction and a polymer conversion reaction on the electrospun product to obtain nanofibers; Step 2, chemically modifying the nanofibers obtained in step 1 so that their surfaces are positively charged, and then mixing them with a negatively charged nanosheet solution to obtain a sheet / fiber composite solution through electrostatic assembly, wherein the components of the sheet / fiber composite solution are the sheet / fiber basic structural units; Step 3, adding a binder to the sheet / fiber composite solution obtained in step 2, stirring evenly to obtain a mixture, directionally freezing the mixture, and obtaining a sheet / fiber composite aerogel by supercritical drying.
3. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 2, characterized in that: In step 1, the polymer precursor is polyborosilazane; the spinning aid is polyvinyl pyrrolidone, and the solvent is a mixture of chloroform and N,N-dimethylformamide; The weight percentage of the polymer precursor in the spinning solution is 30 wt.%, the weight percentage of polyvinyl pyrrolidone is 10 wt.%, the weight percentage of chloroform is 45 wt.%, and the weight percentage of N,N-dimethylformamide is 15 wt.%.
4. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 3, characterized in that: The process parameters of the electrospinning in step 1 are: spinning voltage 15-25 kV, receiving distance 15-20 cm, spinning rate 0.5-1.5 ml / h, spinning needle diameter 0.5-1.0 mm, spinning temperature 20-30° C., and spinning environment humidity 40-60%.
5. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 4, characterized in that: The temperature of the thermal oxidation crosslinking reaction in step 1 is 200-300° C. and the time is 0.5-1 h; The temperature of the polymer conversion reaction in step 1 is 1200-1500° C. and the time is 2-4 hours.
6. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 2, characterized in that: The chemical modifier used in the chemical modification in step 2 is any one of dopamine hydrochloride, hexadecyltrimethylammonium bromide, dodecyldimethylbenzylammonium chloride, ethylenediamine, and hexamethylenetetramine, and the solvent is a mixture of deionized water and anhydrous ethanol.
7. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 6, characterized in that: In step 2, the concentration of the chemical modifier is 10 mg / mL, the mass ratio of deionized water to anhydrous ethanol is 1:1, and the mass ratio of the chemical modifier to the nanofiber is 1:1; The modification time is 6-12h, the modification temperature is 20-50°C, and the stirring rate is 300-600 rpm.
8. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 2, characterized in that: The nanosheets used for the electrostatic assembly in step 2 are any one of graphene, MXene, and MoS2, the concentration of the nanosheet solution is 10 mg / mL, the solvent is deionized water, and the added mass ratio of nanofibers and nanosheets is 1:1-4:
1.
9. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 2, characterized in that: In the step 3, the binder is polyvinyl alcohol, the mass ratio of polyvinyl alcohol to nanosheets is 3:1, the stirring temperature is 70° C., and the stirring time is 12 h.
10. The method for preparing the cyclically compressible and resilient wave-absorbing aerogel according to claim 2, characterized in that: The freezing method in step 3 adopts a two-way freezing process, and the mold used during freezing is made of copper and has a wedge shape.
Citation Information
Patent Citations
Fiber-enhanced aerogel-polymer composite material and preparation method thereof
CN107099117A
Method for preparing 3D porous crosslinked composite aerosol assembled by thermo-bond reinforced nano-fibers
CN108892911A
Preparation method of silicon dioxide nanofiber / MXene composite aerogel with dual protection performance
CN113416054A
Preparation method of graphene / ceramic nanofiber / polyvinyl alcohol hybrid aerogel
CN114409954A
Silicon dioxide nanofiber and graphene composite aerogel as well as preparation method and application thereof
CN116409981A
Cited By
Beta-C3N4-polyaniline / RGO loaded nanofiber wave-absorbing aerogel constructed based on freeze-drying method and preparation method of beta-C3N4-polyaniline / RGO loaded nanofiber wave-absorbing aerogel
CN121510562A